PENGGUNAAN MODEL LEARNING CELL TERHADAP HASIL BELAJAR SISWA MADRADAH - Anas Salahudin; Novian Sukmawati (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study is based on theoretical study which states that the high of the students 'learning outcomes in IPS subjects is influenced by the students' responses to The Learning Cell model. The purpose of this research is to know: (1) Reality of student responses to The Learning Cell model; (2) The reality of their learning outcomes on IPS subjects of the subject of the proclamation of independence of the Republic of Indonesia; (3) Reality of student response relation to cooperative learning model of The Learning Cell type with their learning result in IPS subject. The method used is descriptive method. Data collection techniques with interviews, observation and dissemination of questionnaires and tests. The sample in this study were 22 students. Correlation analysis of both variables using product moment correlation technique, because both variables are normal distribution and regresinya linear. From the results of the analysis, it is known that students' responses to the cooperative learning model of The Learning Cell types fall into the high category with an average value of 3.97. The results of their study on IPS subjects included into the category enough with an average value of 65.54. There is a significant positive relationship between students' responses to the cooperative learning model of The Learning Cell type in relation to their learning outcomes on IPS subjects of the subject of the proclamation of independence of the Republic of Indonesia.